Peran Sekolah Dan Orang Tua Dalam Pelaksanaan Pendidikan Agama Islam Siswa Smp Negeri 3 Yogyakarta Tahun Pelajaran 2013/2014 - Liya Nurul Habibah (Universitas Alma Ata, 2014)
This study aims to determine the role of schools in the implementation of Islamic Education everyday, knowing the parental role in launching the process of teaching and learning activities in schools and daily life, knowing the cooperation of school and parents in launching the process of teaching and learning activities in schools particularly in Islamic Education. This research is a field research. The research method used is qualitative, as the amplifier is also conducting research literature.The results showed that the role of the joint between the school and parents in the process of implementation of Islamic education of children. This is evidenced by the religious activities conducted school received a positive response from parents. The attention given to the students’ parents made the motivation for the students to be able to achieve a good academic record and have good morals in accordance with the guidance of Islam with the support of the school. Some of the activities carried out school aims to assist parents in order to succeed in school education for the students.